Longing in belonging : the cultural politics of settlement - Ilcan, Suzan (Praeger, 2002)
Annotation This book provides fresh insight into the placement, and displacement, of particular social groups, including guest workers, migrants, and immigrants. Ilcan covers the varieties of diasporic relations and the settlements they form, as well as the manifold ways in which they affect traditional practices of settlement. She considers the cultural, economic, and political implications of globalization, evoking the struggle in our "places" of habitation, and the strategies deployed to subvert our habits of settlement.